Serum anti-oxidant capacity and NOx levels in leptopsirosis patients - Wickramasinghe, S.A.; Handunnetti, S.M.; Kalugalage, T.L.; Eugene, E.J.; Gunaratna, R.I.; De Silva, H.J.; Rajapakse, S. (My University, 2012)
Release of reactive oxygen and reactive nitrogen species (ROS and RNS) contribute to increased oxidative stress and also tissues damage which is thought to lead to multi-organ failure in Leptospirosis. The antioxidant capacity (AOC) of serum provides a measure of overall protection against oxidative damage. RNS (ie., nitric oxide (NO ) released is immediately converted to NO2 and NO3 (NOx) and serum NOx levels reflect the level of NO released.